THE ROLE OF PEDAGOGY AND PSYCHOLOGY IN GENERATION FORMATION - Tosheva Madina Sharofiddinova (Лучшие интеллектуальные исследования, 2024)
Abstract: This article contains many definitions of education, but simplified In other words, education is the imparting of general knowledge, the ability to think and reason is the process or actions of formation and direct learning in general.